2006
DOI: 10.1111/j.1567-1364.2006.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

KlADH3, a gene encoding a mitochondrial alcohol dehydrogenase, affects respiratory metabolism and cytochrome content inKluyveromyces lactis

Abstract: A Kluyveromyces lactis strain, harbouring KlADH3 as the unique alcohol dehydrogenase (ADH) gene, was used in a genetic screen on allyl alcohol to isolate mutants deregulated in the expression of this gene. Here we report the characterization of some mutants that lacked or had highly reduced amounts of KlAdh3p activity; in addition, these mutants showed alterations in glucose metabolism, reduced respiration and reduced cytochrome content. Our results confirm that the KlAdh3p activity contributes to the reoxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…When cells were incubated on media supplemented with a certain concentration of allyl alcohol, only those clones with reduced ADH activity were able to grow. It is known that allyl alcohol can be used as a select agent to isolate ADH-deficient mutants of some yeast species, such as S. cerevisiae [19], [24], K. lactis [25], [26] and C. guilliermondii [27]. Similarly, six mutants of C. maltosa Xu316, resistant to 400 mM allyl alcohol, were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…When cells were incubated on media supplemented with a certain concentration of allyl alcohol, only those clones with reduced ADH activity were able to grow. It is known that allyl alcohol can be used as a select agent to isolate ADH-deficient mutants of some yeast species, such as S. cerevisiae [19], [24], K. lactis [25], [26] and C. guilliermondii [27]. Similarly, six mutants of C. maltosa Xu316, resistant to 400 mM allyl alcohol, were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that KlAdh3, like Adh3 of S. cerevisiae (Bakker et al , 2000), participates in an ethanol – acetaldehyde shuttle involved in mitochondrial reoxidation of cytosolic NADPH (Overkamp et al , 2002), and we have recently shown that KlAdh3 affects respiratory metabolism in K. lactis (Saliola et al , 2006), feeding the reduced equivalents to the respiratory chain through the mitochondrial transdehydrogenase KlNdi1 (GonzĂ lez Siso, 2000; Overkamp et al , 2002; Tarrio et al , 2005, 2006). We have also shown that mutations in subunits of the succinate dehydrogenase complex almost completely abolish the expression of KlADH3 (Saliola et al , 2006). Therefore, KlAdh3 seems to be involved in the reoxidation of NAD(P)H during growth on respiratory carbon sources with the exception of ethanol, whereas, as recently reported, KlAdh4 might be the mitochondrial activity devoted to the utilization of the ethanol accumulated during fermentation (Saliola et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol and acetaldehyde freely diffuse across membranes. In yeast mitochondria, Adh3 was shown to be involved in (i) the conversion of acetaldehyde to ethanol with reoxidation of mitochondrial NADH (ethanol-acetaldehyde shuttle) which is important under anaerobic growth (Bakker et al 2000 ; Lertwattanasakul et al 2009 ), (ii) protection from the toxic effects of ethanol, and (iii) cofactors recycling by the conversion of ethanol to acetaldehyde (Saliola et al 2006 ; Suwannarangsee et al 2012 ). Our data show that the overexpression of D. bruxellensis ADH3 enhances the conversion of acetaldehyde to ethanol (higher ethanol and lower acetate yields) under aerobic glucose fermentation.…”
Section: Discussionmentioning
confidence: 99%